1999
DOI: 10.1346/ccmn.1999.0470106
|View full text |Cite
|
Sign up to set email alerts
|

Applying X-Ray Geothermometer Diffraction to a Chlorite

Abstract: Abstract--A new method is proposed for applying the chlorite geothermometer using X-ray diffraction (XRD) data. A linear correlation has been found between the (001) basal spacing of chlorite and its "crystallization" temperature. The basal spacing values were corrected for an increase of AI(IV) with Fe enrichment (Fe/Fe + Mg), when the Fe(II) value of chlorite is > 2.6 in the formula unit. The regression coefficient of the best fit is r = 0.95. Only 2 Bragg lines need to be measured for application of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 29 publications
0
21
2
1
Order By: Relevance
“…Using the measured d (001) values we can estimate the formation temperatures of chamosites based on the method proposed by Battaglia (1999): (1) Hayes, 1970;Curtis et aL, 1985). The field for berthierines, based on 102 published analyses, is also shown.…”
Section: Berthierinementioning
confidence: 99%
“…Using the measured d (001) values we can estimate the formation temperatures of chamosites based on the method proposed by Battaglia (1999): (1) Hayes, 1970;Curtis et aL, 1985). The field for berthierines, based on 102 published analyses, is also shown.…”
Section: Berthierinementioning
confidence: 99%
“…Also, the types of chlorite can reflect the ambient temperatures qualitatively [28,48] . The quantitative relations between the value of interplanar spacing d 001 of chlorites and temperature has been studied by Battaglia [34] . These studies place a firm foundation for the application of chlorite geothermometry.…”
Section: Forming Temperature Of Chloritesmentioning
confidence: 99%
“…The complexity of chlorite's composition can record the information of the changes of the physical and chemical conditions during its formation processes [27][28][29][30][31] . Previous studies indicate that there is a certain linear relationship between the chemical components of chlorites and the temperatures of the geothermal system [32][33][34][35] . This relationship indicates geothermometic features that can be used to acquire the information of thermal evolution of the sedimentary basin.…”
mentioning
confidence: 99%
“…Chlorite group dis plays a wide range of chem i cal com po sition, which can vary de pend ing on the con di tions of for ma tion (e.g., Cathelineau and Nieva, 1985;Bailey, 1988;Cathelineau, 1988;Battaglia, 1999;Schmidt and Livi, 1999;Krzemiñski, 2000;Zimák, 1999;Vidal et al, 2005;Plissart and Féménias, 2009). A gen eral crystallochemical for mula of chlorite can be given as fol lows (de Caritat et al, 1993): where: u + y + z = 6, z = (y -w -x)/2, w fre quently reaches zero, R 2+ usu ally rep re sents Mg 2+ or Fe 2+ , R 3+ typ i cally rep re sents Al 3+ or Fe 3+ , and rep resents struc tural va can cies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Parra et al (2005) ex per i men tally showed that the Si-con tent of chlorite is sen sitive to tem per a ture for the var i ous divariant as sem blages. Chlorite geothermometry has been mod i fied, as by Battaglia (1999), for ex am ple, who exploite X-ray dif frac tion pat terns in chlorite to this end, and by Inoue et al (2009). Given the useful ness of geothermometers in ge ol ogy, this ubiq ui tous min eral pro vides a sim ple and easy means of es tab lish ing con di tions of the host rock for ma tion.…”
Section: Introductionmentioning
confidence: 99%